Communication about spinal muscular atrophy and genetic risk within families: An Australian pilot study. (29th May 2020) - Pieper, Ellen; Sexton, Adrienne; Ryan, Monique M; Forbes, Robin
Abstract : Aim: In families with a child diagnosed with spinal muscular atrophy (SMA), siblings who do not have SMA could still be genetic carriers of the condition. This study is the first to explore how siblings of patients with SMA learn about the condition and their genetic risk. Method: In‐depth, semi‐structured interviews were conducted with several parents and unaffected siblings of people with SMA types II and III in Australia. Thematic analysis was performed. Results: Siblings described learning about SMA gradually over time through conversations with their parents and other sources, including the Internet, biology classes and support groups. Parents and unaffected siblings described challenges in family communication due to the emotional intensity associated with having SMA in the family. Most siblings did not report learning from their family how the inheritance of SMA related to their own genetic carrier risk and possible reproductive implications. Conclusion: Siblings described their parents as being open and honest in communicating about SMA; however, this study found that communication before the age of understanding abstract concepts, in combination with the emotional intensity of SMA, resulted in gaps in knowledge about SMA.